Towards a stable noeuromycin analog with a D-manno configuration: synthesis and glycosidase inhibition of D-manno-like tri- and tetrahydroxylated azepanes. - Deschamp, J; Mondon, M; Nakagawa, S; Kato, A; Alonzi, D; Butters, T; Zhang, Y; Sollogoub, M; Blériot, Y (2012)
Noeuromycin is a highly potent albeit unstable glycosidase inhibitor due to its hemiaminal function. While stable D-gluco-like analogs have been reported, no data are available for D-manno-like structures. A series of tri- and tetrahydroxylated seven-membered iminosugars displaying either a D-manno-or a L-gulo-like configuration, were synthesized from methyl α-D-mannopyranoside using a reductive amination-mediated ring expansion as the key step. Screening towards a range of commercial glycosidases demonstrated their potency as competitive glycosidase inhibitors while cellular assay showed selective albeit weak glycoprotein processing mannosidase inactivation.